2018
DOI: 10.1074/jbc.ra118.003424
|View full text |Cite
|
Sign up to set email alerts
|

Pore properties of Orai1 calcium channel dimers and their activation by the STIM1 ER calcium sensor

Abstract: Store-operated Ca entry signals are mediated by plasma membrane Orai channels activated through intermembrane coupling with Ca-sensing STIM proteins in the endoplasmic reticulum (ER). The nature of this elaborate Orai-gating mechanism has remained enigmatic. Based on the Orai structure, mammalian Orai1 channels are hexamers comprising three dimeric subunit pairs. We utilized concatenated Orai1 dimers to probe the function of key domains within the channel pore and gating regions. The Orai1-E106Q selectivity-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…In line with preserved STIM1 mediated activation of Orai1 H134W-Orai1, also Orai1 H134W-Orai1 S239C exhibited store-dependent activation upon co-expression with STIM1 to a similar extent as for Orai1-Orai1 H134A (Fig 6 f, h). Interestingly, also Orai1 K85E-Orai1 H134A displayed store-operated currents (Fig 6 g), in accordance with the activity of Orai1 K85E-Orai1 dimer published in Cai et al 63 . In contrast, Orai1 E149K -Orai1 H134A and Orai1 L174D -Orai1 H134A remained inactive in the presence of STIM1 (Fig 6 g, h).…”
Section: Cetr-lof Mutants Are Dominant Over Gof Mutants In Orai Dimerssupporting
confidence: 90%
See 2 more Smart Citations
“…In line with preserved STIM1 mediated activation of Orai1 H134W-Orai1, also Orai1 H134W-Orai1 S239C exhibited store-dependent activation upon co-expression with STIM1 to a similar extent as for Orai1-Orai1 H134A (Fig 6 f, h). Interestingly, also Orai1 K85E-Orai1 H134A displayed store-operated currents (Fig 6 g), in accordance with the activity of Orai1 K85E-Orai1 dimer published in Cai et al 63 . In contrast, Orai1 E149K -Orai1 H134A and Orai1 L174D -Orai1 H134A remained inactive in the presence of STIM1 (Fig 6 g, h).…”
Section: Cetr-lof Mutants Are Dominant Over Gof Mutants In Orai Dimerssupporting
confidence: 90%
“…Initially, we generated dimers with one wild-type subunit and one subunit, containing the constitutive MTR-GoF-H134A or -P245L mutation. In contrast to the strong constitutive activity of these point mutations in the homomer, in the heteromer, they allow only store-operated activation in the presence of STIM1 ( Fig 6 h; Supp Fig 10) in line with the store-dependent activation of an Orai1 dimer containing one wild-type and one Orai1 V102A subunit 63 . This indicates that at least more than three GoF mutations within a hexamer are required to induce constitutive activity.…”
Section: Cetr-lof Mutants Are Dominant Over Gof Mutants In Orai Dimersmentioning
confidence: 86%
See 1 more Smart Citation
“…7). Recent studies showed that co-expression of STIM1 with a concatenated heterodimer consisting of WT ORAI1 and ORAI1-E106A in ORAI-SKO cells generated SOCE and membrane currents that were substantially reduced compared with a concatenated heterodimer composed of WT ORAI1 and ORAI1-E106Q 30 . These results suggest that ORAI isoforms heteromerize under native conditions and that Ca 2+ oscillations can be sustained by a minuscule amount of Ca 2+ entry that is below the detectable limit of Fura2.…”
Section: Resultsmentioning
confidence: 99%
“…[38] However, it is still very challenging to establish the structural basis for the formation of the Orai-STIM complex at the activated state, as the fragmented information available is not enough to facilitate spelling out the complete picture of this complicated molecular machinery. [39][40][41][42][43][44][45][46] The pore protein Orai usually assembles as homomultimers, though heterooligomers were also observed. When overexpressed, the hetero-pentameric assembly of subunits could be formed that three Orai1 subunits and two Orai3 subunits integrate into an arachidonic acid-activated channel.…”
mentioning
confidence: 99%